Fibrin Deposition in the Rabbit Kidney Produced by Protease Inhibitors - Beller, F. K; Mitchell, P. S; Gorstein, F (Thrombosis and Haemostasis, 1967)
The infusion of thrombin and the proteolytic inhibitors EACA, AMCHA, PAMBA, Trasylol, Soya and Lima bean trypsin inhibitor as well as ovomucoid, resulted in fibrin deposition in the glomerulus of the rabbit. The distribution is similar in may respects to that observed in the GSP. Renal cortical necrosis did not occur and the fibrin was apparently lysed 24 hrs after infusion. At that time the inhibitors have disappeared from the tissues. It is assumed that the inhibition of the fibrinolytic enzyme system due to these substances, produces a potentiation of thrombin and, therefore, intravascular coagulation. The animals were partly defibrinated without significant alteration in circulating platelets. If several inhibitors were used together, the action was additive and not synergistic was observed. The experiments indicate that the mechanism of fibrin deposition in the rabbit is related to the fibrinolytic capacity of the organism in addition to other factor and is not merely a function of RES blockade (32).